Peak troponin predicts successful weaning from VA ECMO in patients with acute myocardial infarction complicated by cardiogenic shock. Issue 1 (January 2022) - North, Monique; Eckman, Peter; Samara, Michael; Chavez, Ivan; Schmidt, Christian; Garberich, Ross; Hryniewicz, Katarzyna
Background: In patients treated for refractory cardiogenic shock (RCS) following acute myocardial infarction (AMI), predicting successful weaning from veno-arterial extracorporeal membrane oxygenation (VA ECMO) has important implications for decision-making and prognosis. Methods: We performed a retrospective review of adult VA ECMO patients with RCS complicating AMI at our institution from 2010 to 2019. We evaluated use of peak troponin I as a predictor of successful decannulation. Results: Sixty-two patients were analyzed; mean age 61.1 ± 9.8 years, 73% males, 62% presented with STEMI. Forty-five patients were successfully weaned (group I). Seventeen patients did not wean (group II); seven patients received a durable LVAD, 10 died. Patients from group I had significantly lower peak troponin I (89 vs 434 ng/mL, p = 0.0001). Receiver operating characteristic curves showed a peak troponin I cutoff of 400 ng/mL correctly classified patients by weaning status 90% of the time, with associated sensitivity of 71% and specificity of 98%. With each 50 ng/mL increase in troponin I, the likelihood of weaning decreased by 33%. Conclusions: Peak troponin I above 400 ng/mL may be helpful in predicting unsuccessful weaning from VA ECMO support for refractory cardiogenic shock following myocardial infarction and facilitate triage decisions regarding need for advanced therapies.